Effect of an 810 nm Diode Laser on the Healing of a Periapical Abscess - Anbari, Fahimeh; Asfia, Mehrnaz; Forouzani, Gelareh; Talebi Rafsanjan, Katayoun (Journal of Lasers in Medical Sciences, 2021)
Introduction: The golden standard of the treatment of radicular cysts is mainly root canal therapy or surgical excision with apicectomy. The root canals are usually disinfected by the mechanical and chemical actions of instruments and chemical irrigating solutions respectively. To improve the efficacy of the root canal disinfection process, many techniques have been used and many researchers are still trying to reach the quickest and most convenient way to achieve this goal. Diode lasers have shown antibacterial activity on dentinal tubules, and they can penetrate more than 1000 μm into the dentin. Case Presentation: Our patient was a 25-year-old female with an infraorbital abscess caused by a non-vital maxillary canine with periapical radiolucency. After completing the conventional treatment, the optical fiber was inserted into the canal according to the working length previously measured. An 810 nm diode laser at the output power of 4 W was used to irradiate the root canals, with a 300 μm fiber.The lesion was resolved in radiographic follow-ups, 3 and 6 months after the root canal treatment. Conclusion: A combination of conventional root canal therapy and an 810 nm diode laser is an effective treatment for non-vital teeth with periapical lesions. DOI: 10.34172/jlms.2021.03